Joy. - Boubnova, Iara; Lunghi, Enrico (Luxembourg : Casino Luxembourg - Forum d'Art Contemporain Luxembourg, 2005)
Cao Fei ; Creed, Martin ; d'O, Honoré ; Fishkin, Vadim ; Gelatin ; Kogler, Peter ; Koo Jeong-a ; Körmeling, John ; Lin, Michael ; Mercedes, Jill ; Mouillé, Thierry ; Nikolaev, Stefan ; Reiterer, Werner ; Rist, Pipilotti ; Sauerer, Peter ; Sturtevant, Elaine ; Tavasiev, Rostan ; Tsui Kuang-Yu ; Tunick, Spencer ; Wurm, Erwin
biog., ind. tent., gr. tent. p. 59-68
Engels
Frans
Exhibition. Joy. Casino Luxembourg - Forum d'Art Contemporain Luxembourg, 17.12.2005 - 05.03.2006.
boek